2021
DOI: 10.1007/s10439-021-02884-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Computational Analysis of Hemodynamics in Adult Pulmonary Hypertension

Abstract: Pulmonary hypertension (PH) is a progressive disease characterized by elevated pressure and vascular resistance in the pulmonary arteries. Nearly 250,000 hospitalizations occur annually in the US with PH as the primary or secondary condition. A definitive diagnosis of PH requires right heart catheterization (RHC) in addition to a chest computed tomography, a walking test, and others. While RHC is the gold standard for diagnosing PH, it is invasive and posseses inherent risks and contraindications. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…In the intralobar arteries, TAWSS is higher compared to the extralobar arteries in both baseline and CTEPH conditions. This observation is consistent with Pillalamarri et al ( 2021 ) who found that TAWSS increased with increasing distance from the heart based on a computational investigation of patient-specific pulmonary hemodynamics across 32 subjects in distinct WHO groups of PH. The Pillalamarri et al ( 2021 )study included one subject with CTEPH, in whom TAWSS decreased in the distal part of the network, consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…In the intralobar arteries, TAWSS is higher compared to the extralobar arteries in both baseline and CTEPH conditions. This observation is consistent with Pillalamarri et al ( 2021 ) who found that TAWSS increased with increasing distance from the heart based on a computational investigation of patient-specific pulmonary hemodynamics across 32 subjects in distinct WHO groups of PH. The Pillalamarri et al ( 2021 )study included one subject with CTEPH, in whom TAWSS decreased in the distal part of the network, consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…This observation is consistent with Pillalamarri et al(2021) who found that TAWSS increased with increasing distance from the heart based on a computational investigation of patient-speci c pulmonary hemodynamics across 32 subjects in distinct WHO groups of PH. The Pillalamarri et al (Pillalamarri et al 2021)study included one subject with CTEPH, in whom TAWSS decreased in the distal part of the network, consistent with our results.…”
Section: Pulmonary Arterial Parameterssupporting
confidence: 91%
“…differences in time averaged wall shear stress predicted by computational fluid dynamics in patients at risk for or with mild pulmonary hypertension Pillalamarri et al (2021). The redistribution of left-to-right blood flow with posture in the coupled model has implications for prediction of both flow velocity profiles and wall shear stress in computational fluid dynamics models of the major arteries.…”
Section: Discussionmentioning
confidence: 99%